Perlindungan Konsumen Dalam Hal Pelaksanaan Tanggung Jawab Pengusaha Travel Tanpa Izin Operasional - Esy Kurniasih; Teguh Rama Prasja; Anggraini Dwi Milandry (Universitas Pendidikan Nasional, 2022)
The development of the business of public transportation services (trevel) is increasing. In the Rokan Hilir district, there are many illegal entrepreneurs travelling, this has a negative impact on consumer who use these public transportation services. The practical purpose of the article is to find out how the implementation of consumer protection of the responsibility of illegal entrepreneur travelling and what the inhibiting factors in implementation in the Tanah Putih district, at Rokan Hilir. This research is included in the type of observation research. The object of this research is to examine consumer protection against the implementation of the responsibilities of travel entrepreneurs without an operational permit in the Tanah Putih district, at Rokan Hilir, which is analyzed based on Law Number 8 of 1999 concerning Consumer Protection. Therefore, the type of research the author uses is observation research, so in this study, the author uses primary data and chooses the census method so that the researcher uses the entire population as respondents.The result of this study, First, indicate that the responsibility of illegal travel entrepreneurs has not been carried out optimally. Second, inhibiting factors the implementation, because the government needs to be more serious and consistent in implementing regulations that have been made. In addition, there is a lack of awareness and understanding of consumer regarding the application of existing rule.